The peculiarities of anatomical organization of some organs in Rorippa palustris (L.) Bess. (Cruciferae) - Shabalkina S. (Zenodo, 2013)
The anatomical organization of root, stem and leaves of generative exemplars of Rorippa palustris (L.) Bess., which grow in the southern taiga of Kirov region has been investigated.